2022
DOI: 10.3390/healthcare10091640
|View full text |Cite
|
Sign up to set email alerts
|

A Brief mHealth-Based Psychological Intervention in Emotion Regulation to Promote Positive Subjective Well-Being in Cardiovascular Disease Patients: A Non-Randomized Controlled Trial

Abstract: The emotional impact that a cardiovascular disease may have on a person’s life can affect the prognosis and comorbidity of the disease. Therefore, emotion regulation is most important for the management of the disease. The aim of this study was to analyze the effectiveness of a brief mHealth psychological intervention in emotion regulation to promote positive subjective well-being in cardiovascular disease patients. The study sample (N = 69, 63.7 ± 11.5 years) was allocated to either the experimental group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
1
2
0
Order By: Relevance
“…This means that higher levels of positivity corresponded to lower levels of anxiety, depression, and psychological discomfort, ultimately leading to greater well-being. These findings align with previous research, underscoring the significance of positivity in the psychological well-being of CVD patients [ 11 , 18 , 19 ]. Maintaining a positive outlook can help prevent emotional states that may become pathological when prolonged, such as elevated levels of anxiety and depression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This means that higher levels of positivity corresponded to lower levels of anxiety, depression, and psychological discomfort, ultimately leading to greater well-being. These findings align with previous research, underscoring the significance of positivity in the psychological well-being of CVD patients [ 11 , 18 , 19 ]. Maintaining a positive outlook can help prevent emotional states that may become pathological when prolonged, such as elevated levels of anxiety and depression.…”
Section: Discussionsupporting
confidence: 91%
“…Recent research has shown the association and relevance of psychological well-being or distress among patients with CVD [ 11 , 18 , 19 ]. Studies have found that increased levels of well-being were related to improved CVH [ 11 ] and lower odds of mortality due to a cardiac event [ 6 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis [45] showed that interventions-mindfulness, cognitive approaches, and other psychological interventions-were particularly effective in increasing subjective (hedonic) wellbeing. Additionally, a gratitude intervention in women found that participants had greater life satisfaction and lower diastolic blood pressure [46], while another eHealth intervention in patients with CVD was found to improve subjective wellbeing [47]. Furthermore, healthcare providers may benefit from considering patients' subjective wellbeing and SRH when evaluating and managing those at risk for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%